The Implementation of NodeMCU ESP8266 for Smart Lamp in the Cilacap State Polytechnic Campus Area - Saepul Rahmat; Anna Nurdiasari; Zaenurrohman Zaenurrohman (Politeknik Negeri Malang, 2022)
Lamps are household electrical devices. In general, the lights are controlled through switches which require the user to move towards the switch to turn the lights on/off. To save time, lights can be controlled via the internet of things using the NodeMcu ESP8266. The purpose of making a smart lamp using the NodeMCU ESP8266 is to make it easier to turn it on and off with a smartphone without the need to look for a switch. This smart lamp can be controlled via a virtual button on the Blynk application or based on a set clock. The results obtained from the design of this tool are that the smart lamp will turn on at 8.00 AM and will turn off automatically at 3.00 PM, or by pressing the virtual button on Blynk. There is a slight delay when the lights will turn on or off, this is caused by the strength of the internet from the wifi connected to the ESP8266.